Complete mitogenome of the Cape petrel Daption capense from Barton Peninsula, King George Island, Antarctica. Issue 1 (2nd January 2019) - Jung, Jin-Woo; Lee, Hyoungseok; Choi, Han-Gu; Kim, Jeong-Hoon
Abstract: The Cape petrel Daption capense, a seabird, is observed throughout the southern hemisphere including the Antarctic region. Herein, we report the complete mitogenome of Cape petrel with the GenBank accession number MH924023 to elucidate the genetic characteristics of this genus. The mitogenome is 17, 312 bp long and comprises 13 protein-coding genes (PCGs), two rRNA genes, and 22 tRNA genes. The overall base composition of the 13 PCGs is as follows: A (31.1%), C (30.3%), T (25.4%), and G (13.2%), with a GC content of 43.5%. The results provide useful information for further genetic studies in Procellariiformes.